Posterior restorations with composite resin in patients with corrosive wear – a clinical case (Research, Society and Development, 2023)
For patients with loss of vertical dimension of occlusion caused by parafunctional habits associated with acidic food intake, care must be taken when choosing the restorative material. The composite resin besides being a low-cost material, is a material that has better indication for treatment not only for optimum comfort, but for increased longevity under study, providing better cost-benefit from the materials of choice. However, one should know well about conditioning, adhesion and composite resin, including finishing and polishing. The main objective of this research was to report a clinical case of a patient with loss of vertical dimension of occlusion caused by parafunctional habits. During the clinical case described in the article, we can analyze research that proves that the composite resin for posterior cases is better, especially when there are multiple cases of wear and parafunction, and we can also analyze the technique used and the predictability in the treatment, causing more comfort for the patient and the Surgeon Dentist.